2022
DOI: 10.3389/fmed.2022.828695
|View full text |Cite
|
Sign up to set email alerts
|

How Do Family Physicians Perceive Their Role in Providing Pre-exposure Prophylaxis for HIV Prevention?–An Online Qualitative Study in Flanders, Belgium

Abstract: Introduction:In Belgium, the provision of pre-exposure prophylaxis (PrEP) for HIV prevention is centralized in specialized HIV clinics. Engaging family physicians in PrEP care could help scale-up its delivery and reach underserved populations. The objective of this study was to gain insight into family physicians' self-perceived roles in providing PrEP.MethodsWe conducted 16 online group discussions with a total of 105 Flemish family physicians, between November 2020 and February 2021. A brief online questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(54 reference statements)
1
3
0
Order By: Relevance
“…The top three barriers that impacted our Australian GPs participants prescribing of PrEP were difficulty identifying clients who would benefit from PrEP, lack of knowledge regarding PrEP, and lack of time to adequately counsel regarding PrEP. These results are comparable with the literature, with the main barriers identified in studies as lack of knowledge regarding PrEP and difficulty identifying clients at risk of HIV (8, 10, 11, 12, 19). Difficulty identifying clients who would benefit from PrEP could be addressed by having GP clinics collect certain demographics as part of client registration.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The top three barriers that impacted our Australian GPs participants prescribing of PrEP were difficulty identifying clients who would benefit from PrEP, lack of knowledge regarding PrEP, and lack of time to adequately counsel regarding PrEP. These results are comparable with the literature, with the main barriers identified in studies as lack of knowledge regarding PrEP and difficulty identifying clients at risk of HIV (8, 10, 11, 12, 19). Difficulty identifying clients who would benefit from PrEP could be addressed by having GP clinics collect certain demographics as part of client registration.…”
Section: Discussionsupporting
confidence: 88%
“…Past studies have identified several barriers to PrEP prescribing among GPs. Barriers include lack of knowledge regarding PrEP, inability to identify clients at risk of HIV, and concern that PrEP use may increase the incidence of other STIs (8, 9, 10, 11, 12). An Australian GP questionnaire found the main barriers to PrEP prescribing were lack of experience with antiretrovirals and lack of guidelines for prescription (13).…”
Section: Introductionmentioning
confidence: 99%
“…Such initiatives will distribute the workload more evenly across health system actors, improve (timely) access to PrEP and ensure more client‐centred care. In particular, previous research in Belgium shows that FPs are willing to be more involved in PrEP care, and that about half of the PrEP users would accept follow‐up visits with their FP [52, 57]. While we observed the emergence of informal collaborative care models between specialized services and FPs in at least one HIV clinic, other clinics were waiting for such models to be first legitimized by reimbursement regulations before implementing them.…”
Section: Discussionmentioning
confidence: 75%
“…To address this, a centralised PrEP registry should be established, and a de-centralisation of PrEP provisions to encourage other medical doctors, including GPs, deems necessary and should be implemented. These approaches align with practices in other European countries like France [10] and Belgium [21], and the elimination programmes of other STIs, such as hepatitis C virus [22]. In turn, the formal provision and uptake of PrEP would be enhanced to support ending the HIV epidemic.…”
Section: Discussionmentioning
confidence: 86%